Resilience and adaptivity in the management of workplace disruption for the service sector - Kufuor, A. (Cranfield University, 2007)
In the last two decades the service sector has dominated the UK economy. Recently, performance and service quality delivery has become a critical issue to the sustainability of businesses in this sector. Disruption to day-to-day operations is increasingly becoming an emergent pattern for organizations across this sector. This has implications for how service organisations structure and organize to deliver efficient and uninterrupted services to clients and stakeholders. Managers and staff within the service sector have been portrayed as struggling to deal with the impact of occurrences of unexpected change and uncertainty on their business operations. Literatures from organizational learning, change management and organizational crisis are drawn upon to develop this study. Concepts of resilience and adaptive capacity form a framework for exploring disruption occurrences on daily operations in the service sector. Investigations are carried out into the experiences of managers and staff to disruption occurrences. Organizational barriers to individual response are examined. Target groups for the study are drawn mainly from the finance, telecommunications, aerospace and defence related sectors. Research methodology and data analysis is based on the grounded theory approach. Fieldwork activity is undertaken in three phases over a twenty-four month period. Twenty six in-depth interviews with senior managers are carried out and two hundred postal questionnaires are administered. There are three main outcomes of the study. These are; i) core categories of disruption & core categories of response behaviour, ii) the Codar Dial; mapping core disruption categories and typical behaviour in response, iii) the five (5) 'C' drivers for enhancing resiliency in dealing with occurrences of disruption. Findings contribute to current knowledge on the concept of disruption and organizational behaviour in management studies. The research contributes also to the fields of change management and organizational learning. The findings have implications for service sector managers in relation to work structures and human resource practices at the management and individual level.